Pengaruh Expressive Writing Therapy Terhadap Stres Pada Remaja Korban Bullying di SMP Kecamatan Koto Tangah Kota Padang - Monalia Arisandi; Dewi Eka Putri; Feri Fernandes (Jurnal Ners, 2025)
Bullying behavior often occurs among adolescents. One of the psychological effects of bullying on victims is stress. One way to address this problem is through expressive writing therapy. The purpose of this study was to examine the effect of expressive writing therapy on stress in adolescent victims of bullying. The research design used was quasi-experimental with a pretest-posttest with control group design. The sample consisted of 38 participants in the intervention group and 38 in the control group, selected using purposive sampling. The instrument used was the Depression, Anxiety, and Stress Scale (DASS 21) for stress-related questions. The study was conducted at a junior high school in Kecamatan Koto Tangah , Kota Padang, in 2025. The results showed that in the intervention group, the average stress score decreased from 10.71 to 6.21, with a difference of 4.50 and a p-value of 0.000, indicating a significant difference in average stress levels between the intervention group before and after receiving expressive writing therapy. There was a significant effect of expressive writing therapy on stress in the intervention group, as evidenced by a p-value of 0.000. It is hoped that expressive writing therapy can be applied to adolescents who are victims of bullying and have stress issues.